Beyond the Business Case: The Need for Both Utility and Justice Rationales for Increasing the Share of Women on Boards. (27th June 2015) - Seierstad, Cathrine
Abstract: Manuscript type: Empirical Research Question: In the context of the recent introduction of gender representation regulations (quotas) for boards in public limited companies (PLCs) in Norway, this article explores how gender quotas designed to increase the share of women in senior positions are rationalized and/or justified by those who benefit, and asks: what arguments do the beneficiaries of quotas tend to use when discussing their usefulness? Research Findings/Insights: Drawing on qualitative interview data from 19 female non‐executive board members, the article illustrates how women draw on utility, mainly the "business case, " and individual justice arguments both in support of quotas and to justify their use in helping women attain board positions. Further, it highlights how issues of merit and of gender are entangled with these arguments in often contradictory ways. In so doing, the article challenges and complicates some of the key critiques of gender quotas often found in the public and academic debates. Theoretical/Academic Implications: This article advances theory around the intersection of justice and utility arguments in relation to the use of quotas to increase diversity on boards. Moreover, this article provides empirical support by demonstrating how "the first wave" of women affected by quotas are legitimizing their role on boards in a context in which their role is in question. In addition, this article advances the literature regarding women on boards by demonstrating the need for a discourse about political strategies, such as quotas on boards, that goes beyond the narrow understanding of the business case that has until now dominated public, political, and academic debates. In particular, this article argues for the need to build on both utility and justice logic when making a case for increasing the share of women on boards. Practical Implications: With the current focus on how to increase diversity and the share of women on boards, this study highlights the importance of regulation as well as the importance of reframing the debate using utility and justice lines of arguments rationalized by merit arguments.